Viability and photosynthetic activity of lichens in extreme environments: results from a global transect to Mars simulation and space exposure - de Vera, Jean Pierre Paul; Onofri, S.; de la Torre, R.; Rabbow, Elke; Horneck, G.; Ott, S. (2010)
A characterisation of a global transect of lichen habitats from the European Alps to Mediterranean Mountain region and to the North Victoria Land Mountains in Antarctica shows the adaptation and colonizing strategies of these symbiotic microorganisms in extreme environments which are often described as Mars analogue areas. Numerous lichens are able to live and to maintain the photosynthetic activity under these harsh conditions, which are characterized by low temperatures, dryness and UV radiation fluxes. Some lichen species are even able to survive simulated and real space conditions. Many tests after space exposure on the satellite FOTON M3 and on the ISS have shown their capacity to maintain physiologic activity, photosynthesising activity and their capacity to germinate and grow after being exposed to space parameters. Further tests under Martian conditions with simulation of a Mars atmosphere with Martian temperature and humidity profiles and a Martian UV- radiation spectrum with limited quantity of water supply have shown maintained photosynthesising activity. In addition to the results obtained by field studies the results from space and Mars simulation experiments are valuable for determination of habitability of a planet and for the search for possible life supporting habitats on terrestrial planets like Mars.